Media Sosial Instagram Sebagai Media Informasi Klub Internal Persebaya - Supriyono Supriyono (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
Instagram social media is a new media that is currently used by the public in finding and getting information. One of them is the social media Instagram @ligapersebaya which is used by the People of Surabaya City as a source of football information. The style of language, type of information and features used by Instagram @ligapersebaya in conveying football information enjoyed by the people of Surabaya City varies. This research aims to find out how Instagram @ligapersebaya as a source of football information for the people of Surabaya City. Instagram @ligapersebaya able to meet the information needs of informants and viewed from the point of view of Media Rrichness Theory Instagram @ligapersebaya managed to meet four factors measuring the wealth of a media. The conclusion of this study is that Instagram @ligapersebaya with the use of Instagram features, the style of language used, the type of information provided is able to meet the football information needs of the people of Surabaya City.